INEFFECTIVE PUBLIC PARTICIPATION FOR EIA: THE CAUSE OF ENVIRONMENTAL ISSUES IN MALAYSIA? - Makmor, Maisarah; Salleh, Hafez; Nordin, Nikmatul Adha (Journal of Surveying, Construction and Property, 2020)
Environmental Impact Assessment (EIA) foster communication between participators to yield a more environmentally sound decision for a proposed development. Public participation is an integral element in EIA to ensure a successful EIA. Effective public participation encourages community empowerment, fair and democratic decisions and reduce thus avoid public confrontation and delay. Effective public participation is one of the key pillars to achieve effective EIA. Environmental issues are known to be the negative outcome of a poorly implemented EIA process. This paper discusses seven environmental cases that were produced from ineffective application of EIA such as Bakun Dam, Murum Dam, Baram Dam, bauxite mining in Kuantan, gold mining in Bukit Koman, sturgeon farming in Kuala Tahan and Lynas plant. The seven cases focused on the lack of public participation in the administration of EIA. Public objections and protests were results of ineffective public participations and ineffective EIAs in the chosen cases. Four out of seven cases have made substantive results where the projects stopped or ceased due to the public objections. Meanwhile, the three cases went on till today. Conclusively, these cases has shown that public participation in EIA is a valuable tool which encourages transparent decision-making process and defies corrupted influences.